VD_FINDINFO HC / 2018 / 1107 vom 5. November 2018 - VD Tribunal cantonal (2018)
SUSPENSION DE LA PROCÉDURE, DEMANDE RECONVENTIONNELLE, APPEL EN CAUSE, LITISPENDANCE | 126 CPC (CH), 63 al. 1 CPC (CH), 81 al. 1 CPC (CH), 85 CPC (CH)